Glycogen synthase kinase‐3β in patients with bipolar I disorder: results from a prospective study. (21st June 2016) - Jacoby, Anne S; Munkholm, Klaus; Vinberg, Maj; Joaquim, Helena GP; Talib, Leda L; Gattaz, Wagner F; Kessing, Lars V
Abstract : Objectives: The enzyme glycogen synthase kinase‐3β (GSK3β) is involved in the mechanisms of action of lithium and may play a role in relation to affective states in bipolar disorder. The objectives of the present study were to compare the activity of GSK‐3β (measured as levels of phosphorylated GSK‐3β [p‐GSK‐3β]) between patients with bipolar disorder in the euthymic state and healthy control subjects, and to investigate whether GSK‐3β activity varies with affective states in patients with bipolar I disorder. Methods: In a prospective 6–12‐month follow‐up study, we investigated state‐specific, intraindividual alterations in the activity of GSK‐3β in 60 patients with bipolar I disorder with an acute severe manic index episode and in subsequent euthymic, depressive and manic states and compared this with repeated measurements in healthy control subjects. Data were analyzed using linear mixed‐effects models. Results: From baseline to the end of follow‐up, blood samples were drawn from the 60 patients during 181 affective states, comprising 60 manic, 11 mixed, 23 depressive, and 87 states of euthymia. A total of 69 blood samples were drawn from 35 healthy control subjects, with two samples from the same subject taken three months apart. In mixed‐model analysis, p‐GSK‐3β was decreased in the euthymic state of subjects with bipolar disorder compared with healthy control subjects ( b =0.63, 95% confidence interval [CI]: 0.42–0.96, P =.03). In addition, p‐GSK‐3β varied with affective states, being increased in depressive ( b =1.68, 95% CI: 1.08–2.62, P =.02) and mixed ( b =2.07, 95% CI: 1.12–3.84, P =.02) states but not in mania compared with euthymia. Conclusions: The activity of GSK‐3β is altered in euthymic bipolar disorder compared with healthy control subjects and varies with affective states.